Improving Engagement: Integrating Assistive Technology in Early Literacy. (November 2021) - Marsh, Kathryn L.; Schladant, Michelle; Sudduth, Christina; Shearer, Rebecca; Dowling, Monica; Natale, Ruby
Although there are documented benefits and legislative mandates for children from birth through age 22, assistive technology (AT) is highly underused, especially among young children (Dunst & Trivette, 2011). One of the main reasons for this underuse is that while teachers are legally required to provide AT for children with disabilities, many teachers do not have the knowledge, confidence, or skills needed to provide AT to support early literacy instruction (Dean, 2020; Hilaire & Gallagher, 2020; Temple, 2019). This article identifies the benefits of AT during early literacy instruction and describes how teachers can integrate practical AT tools and strategies into early literacy instruction using a widely utilized framework call the SETT (Student Environment Task Tool; Zabala, 1995) Framework. The authors aim to provide free professional development resources to improve teachers integration of AT in their classrooms to enhance opportunities for young children with disabilities to meaningfully participate in everyday literacy activities.